A cross-sectional study of pre-travel health-seeking practices among travelers departing Sydney and Bangkok airports - Heywood Anita E; Watkins Rochelle E; Iamsirithaworn Sopon; Nilvarangkul Kessarawan; MacIntyre C (BMC, 2012)
Abstract Background Pre-travel health assessments aim to promote risk reduction through preventive measures and safe behavior, including ensuring travelers are up-to-date with their immunizations. However, studies assessing pre-travel health-seeking practices from a variety of medical and non-medical sources and vaccine uptake prior to travel to both developing and developed countries within the Asia-Pacific region are scarce. Methods Cross-sectional surveys were conducted between July and December 2007 to assess pre-travel health seeking practices, including advice from health professionals, health information from other sources and vaccine uptake, in a sample of travelers departing Sydney and Bangkok airports. A two-stage cluster sampling technique was used to ensure representativeness of travelers and travel destinations. Pre-travel health seeking practices were assessed using a self-administered questionnaire distributed at the check-in queues of departing flights. Logistic regression models were used to identify significant factors associated with seeking pre-travel health advice from a health professional, reported separately for Australian residents, residents of other Western countries and residents of countries in Asia. Results A total of 843 surveys were included in the final sample (Sydney 729, response rate 56%; Bangkok 114, response rate 60%). Overall, pre-travel health information from any source was sought by 415 (49%) respondents with 298 (35%) seeking pre-travel advice from a health professional, the majority through general practice. Receipt of a pre-travel vaccine was reported by 100 (12%) respondents. Significant factors associated with seeking pre-travel health advice from a health professional differed by region of residence. Asian travelers were less likely to report seeking pre-travel health advice and uptake of pre-travel vaccines than Australian or other Western travelers. Migrant Australians were less likely to report seeking pre-travel health advice than Australian-born travelers. Conclusions This study highlights differences in health-seeking practices including the uptake of pre-travel health advice by region of residence and country of birth. There is a public health need to identify strategies targeting these travel groups. This includes the promotion of affordable and accessible travel clinics in low resource countries as traveler numbers increase and travel health promotion targeting migrant groups in high resource countries. General practitioners should play a central role. Determining the most appropriate strategies for increasing pre-travel health preparation, particularly for vaccine preventable diseases in travelers is the next stage in advancing travel medicine research.